Classifying sports medicine diagnoses: a comparison of the International classification of diseases 10-Australian modification (ICD-10-AM) and the Orchard sports injury classification system (OSICS-8). Issue 12 (23rd November 2005) - Rae, K; Britt, H; Orchard, J; Finch, C
Abstract : Background: The International classification of diseases 10-Australian modification (ICD-10-AM) and the Orchard sports injury classification system (OSICS-8) are two classifications currently being used in sports injury research. Objectives: To compare these two systems to determine which was the more reliable and easier to apply in the classification of injury diagnoses of patients who presented to sports physicians in private sports medicine practice. Methods: Ten sports physicians/sports physician registrars each coded one of 10 different lists of 30 sports medicine diagnoses according to both ICD-10-AM and OSICS-8 in random order. The coders noted the time taken to apply each classification system, and allocated an ease of fit score for individual diagnoses into the systems. The 300 diagnoses were each coded twice more by "expert" coders from each system, and these results compared with those of the 10 volunteers. Results: Overall, there was a higher level of agreement between the different coders for OSICS-8 than for ICD-10-AM. On average, it was 23.5 minutes quicker to complete the task with OSICS-8 than with ICD-10-AM. Furthermore, there was also higher concordance between the three coders with OSICS-8. Subjective analysis of the codes assigned indicated reasons for disagreement and showed that, in some instances, even the "expert" coders had difficulties in assigning the most appropriate codes. Conclusions: Based on the results of this study, OSICS-8 appears to be the preferred system for use by inexperienced coders in sports medicine research. The agreement between coders was, however, lower than expected. It is recommended that changes be made to both OSICS-8 and ICD-10-AM to improve their reliability for use in sports medicine research.